The Use of Short Story as A Teaching Vocabulary Resource to The Second Grade of Babul Khaer Islamic Boarding School Bulukumba - Nasyirah, Ummul; Rahman, Asfah; Wello, Muhammad Basri (Fakultas Sastra - Universitas Muslim Indonesia, 2023)
The purpose of this study was to investigate the effectiveness of using short stories as a teaching vocabulary resource for second grade students at Babul Khaer Islamic Boarding School Bulukumba. The study employed a quasi-experimental design with a pretest-posttest control group to evaluate the impact of short stories on students' vocabulary acquisition. The participants in this research were 16-member classes of second-grade students (XI. Exact-2 as the experimental class and XI. Social Science-2 as the control class). The study instrument consisted of a test and a questionnaire. This data showed that the pre-test mean score for the experimental class was 47.31 and that it increased to 56.75 on the post-test. The findings revealed that students in the experimental group, who were exposed to short stories, significantly improved their vocabulary compared to the control group. The results suggest that short stories can be a valuable resource for vocabulary instruction in second grade students. Furthermore, the study highlights the potential implications of integrating short stories into the curriculum, including enhanced student engagement, improved critical thinking skills, and enriched cultural understanding. Additional research is needed to further explore the long-term effects of using short stories for vocabulary instruction and its impact on students' overall language development.